Delay to Establish the Diagnosis, and the Clinical Picture, Radiologic Findings and Bacteriology Results in Pulmonary Tuberculosis - Chávez Díaz, Tania (1998)
The relationship between the delay to establish the diagnosis of tuberculous disease, and the clinical picture, radiologic findings and smear sputum tests results in smear-positive cases of TB at the Hospital Nacional Daniel Alcides Carrión - Callao, in 1996, was analized. A total of 130 patients (70 males, 30,96 ± 15,05 years-old) were studied. The Mean Delay to Establish the Diagnosis (MDED) was 60,27 ± 54,94 d, being 75,50 ± 66,38 d the largest time (patients from the ER). MDED was correlated with the following: procedence (30% from department of pneumology, 70% the remainder); type of sputum [commonest: mucous type 39,23%, Mean Time (MT) = 58,44 ± 44,95 d]; weight loss (commonest: mild < 5 kg: 48,46%, MT = 53,12 ± 42,91 d); hemoptysis (commonest: mild < 200 mL/d, 22,31%; MT = 84,81 ± 63,76 d); crackles: 73,08%, MT = 59,71 ± 54,51 d; subcrepits: 30,77%, MT = 47,00 ± 45,37 d; cavities: single 27,69%, MT = 88,83 ± 57,77 d; one-sided 31,54%, MT = 90,13 ± 67,72 d; smear-microscopy results (1+): 39,23%, MT = 66,09 ± 54,33 d, (2+): 30%, MT = 39,35 ± 33,60 d and (3+): 30,77%, MT = 73,25 ± 65,93 d. There were positive correlations between the variables in all of cases. The delay between the onset of symptoms and the diagnosis in non-treated patients was 60,27 ± 54,94 d. Clinic, radiologic and microscopic features showed a positive correlation with the MDED. Finally, we show that, in all cases, after 60 days since the onset of symptoms, there was an increase in the severity, being a preventable and predictible group.